Pengaruh Pengaruh Pemahaman Konsep Dasar Akuntansi dan Pengalaman Praktik Kerja Lapangan terhadap Kesiapan Siswa dalam Bekerja Pada Kelas XII Program Keahlian Akuntansi dan Keuangan Lembaga di SMK Negeri 1 Tabanan - Luh Putu Widhia Lestari; M. Rudi Irwansyah (Ekuitas: Jurnal Pendidikan Ekonomi, 2023)
The purpose of this study was to be able to determine the effect of understanding the basic concepts of accounting and practical experience of field work on student work readiness. This study used a quantitative research type with a research population of class XII AKL students at SMK Negeri 1 Tabanan, totaling 53 students using a proportional random sampling technique. Based on the results of research (1) there is a positive and significant influence between understanding the basic concepts of accounting on student work readiness as indicated by a sig value <0.05 (0.002 <0.05). (2) there is a positive and significant relationship between practical field work experience and student work readiness with a sig <0.05 (0.000<0.05). (3) there is an influence between understanding the basic concepts of accounting and practical experience of field work simultaneously on student work readiness with a sig value <0.05 (0.000<0.05). Based on the findings and results of the research, the implications that can be given are (1) students increase their knowledge and master the areas of expertise they are interested in, one of which is accounting. (2) make good use of field work practices as a vehicle for skills training. (3) in order to achieve high job readiness, it is necessary to master knowledge and skills through actual training related to the field of work of interest.